Effective mass of a migrating interface - Xinyuan Song; Chuang Deng (Proceedings of the National Academy of Sciences, 2026)
Interfaces are ubiquitous in materials and play a central role in microstructural evolution and material properties. Although interface migration has been studied for more than a century and remains an active field, several foundational assumptions of interface kinetics remain largely untested. In particular, interfaces are commonly treated as massless objects governed by overdamped dynamics. In this study, we show that grain boundaries exhibit measurable inertial behavior under high-frequency oscillatory driving. We introduce a quantitative method to extract an effective interface mass from the phase lag between the applied force and the interface velocity and find that this mass scales with the atoms participating in boundary migration. Using this framework, we identify regimes in which inertial effects significantly modify interfacial kinetics, especially at frequencies relevant to thermal fluctuations. These results challenge the conventional overdamped description and establish effective interface mass as a key ingredient in a physically complete theory of interface migration.